2019
DOI: 10.1002/ange.201907695
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐Ferroelectric for High Efficiency Overall Water Splitting under Ultrasonic Vibration

Abstract: Piezocatalysis,converting mechanical vibration into chemical energy,h as emerged as ap romising candidate for water-splitting technology.H owever,t he efficiency of the hydrogen production is quite limited. We herein report welldefined 10 nm BaTiO 3 nanoparticles (NPs) characterized by al arge electro-mechanical coefficient which induces ah igh piezoelectric effect. Atomic-resolution high angle annular dark field scanning transmission electron microscopy(HAADF-STEM) and scanning probe microscopy(SPM) suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…After 5 min of irradiation with ultrasound (US; 1 MHz, 1 w/cm 2 , 50% duty cycle), little O 2 production was observed for the 200 nm BTO group and BTO nanowire group, which should be due to the piezoelectric potential in both of these groups not reaching the energy for water splitting (1.23 eV). 27 In contrast, the O 2 concentration in the US+P-BTO group was nearly 1.5 times higher than that in the control group, P-BTO group, US group, the 200 nm BTO group, and BTO nanowire group. These results suggested that O 2 generation was attributed to the P-BTO nanoparticles irradiated by ultrasound, indicating that ultrasmall barium titanate could be used for the O 2 production in tumor treatment.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…After 5 min of irradiation with ultrasound (US; 1 MHz, 1 w/cm 2 , 50% duty cycle), little O 2 production was observed for the 200 nm BTO group and BTO nanowire group, which should be due to the piezoelectric potential in both of these groups not reaching the energy for water splitting (1.23 eV). 27 In contrast, the O 2 concentration in the US+P-BTO group was nearly 1.5 times higher than that in the control group, P-BTO group, US group, the 200 nm BTO group, and BTO nanowire group. These results suggested that O 2 generation was attributed to the P-BTO nanoparticles irradiated by ultrasound, indicating that ultrasmall barium titanate could be used for the O 2 production in tumor treatment.…”
Section: Resultsmentioning
confidence: 82%
“…As a result, the imbalanced charges will induce redox reaction with the water molecules to produce O 2 and ROS (Figure 3a). 27 A dissolved oxygen meter (AZ8403, China) was used to measure the O 2 generation in deoxygenated deionized water. Six groups were set to verify the piezocatalytic water-splitting ability of P-BTO nanoparticles (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations